PERHITUNGAN PREMI ASURANSI JIWA MENGGUNAKAN GENERALIZED LINEAR MIXED MODELS - Siti Alfiatur Rohmaniah; Novita Eka Chandra (Jurnal Ilmiah Teknosains, 2018)
The price of life insurance premiums for each person depends on the probability of death, not only based on age and gender as offered by an Indonesian insurance company.  The purpose of this study is to determine premium prices on underwriting factors and frailty factors using Generalized Linear Mixed Models (GLMM). GLMM is used for modeling a combination of fixed effect heterogeneity (underwriting factors) and random effects (frailty factors) between individuals. The data used longitudinal data about underwriting factors that have Binomial distribution are taken from the Health and Retirement Study and processed using R software. Because the data used by survey data within an interval of two years, so the probability of death is obtained for an interval the next two years. Underwriting factors that have a significant effect on the probability of death are age, alcoholic status, heart disease, and diabetes. As a result, is obtained the probability of death models each individual to determine life insurance premium prices. The premium price of each individual is different because depends on underwriting factors and frailty. If frailty is positive, it means that a person level of vulnerability when experiencing the risk of death is greater than negative frailty.